Intervention in professional dance students to increase mental health- and nutrition literacy: A controlled trial with follow up - Mathisen, Therese Fostervold; Sundgot-Borgen, Christine; Anstensrud, Beate; Sundgot-Borgen, Jorunn (Frontiers in Sports and Active Living, 2022)
Introduction: There is a need to change a culture within the art of dance, which associates to injuries and mental health issues. This study evaluates an intervention designed to increase mental health literacy, enhance knowledge and reduce symptoms and consequences of low energy availability, and strengthen understanding on sports nutrition and recovery strategies, in dance students of mixed genders. Material and Methods: A total of 125 dance students received three workshops, with 39 arts & crafts students serving as references. Results were evaluated by the Eating Disorder Examination-questionnaire, the Low Energy Availability in Females-questionnaire, the Hopkins Symptom Check List, and questions on mental health literacy, sports nutrition- and recovery knowledge. Results: Dance students achieved sustained improvements in mental health- and nutrition knowledge, and temporary improvements in driven exercise (i.e. performing exercise because of a compulsive drive). No other benefits were identified from the intervention. Conclusion: Our findings indicate the need for a more continuous education program to reduce the burden of symptoms of mental health challenges and low energy availability in professional dance students. Such approaches may not simply improve the mental health in dance students, but potentially also prevent the high frequency of injuries.